Islam as a Tool in The Politics of Middle East - Sameen Ahmad; Sara Qazi; Dr. Adul Wahab Jan (Al Manhal Research Journal, 2024)
This paper traces the significant role of Islam in the political dynamics of the Middle East from its advent to the present day. Originating in Medina, Islam rapidly expanded beyond the Arabian Peninsula, influencing and reshaping he religious and political landscape of neighboring regions, including Syria, Palestine, Yemen, Iraq, and the Persian Empire. The study outlines the historical evolution of Islam’s political influence, highlighting the early conquests and the establishment of Islamic governance across diverse territories. Central focus is placed on the enduring sectarian divide between Sunni Shiite Muslims which began in the era of Hazrat Ali and Ameer Muavia. This schism led to the crises in middle east and shaped the region ‘s political landscape. The sectarian divide fueled ongoing rivalries, proxy wars, and struggles for regional dominance. The paper argues that Islam has been consistently practiced as a political tool, during Middle East crises, to support their political agendas. Overall, the research highlights Islam’s continuous and active role in the politics of Middle East, underscoring its influence on both historical and contemporary geopolitical development.